THE MEANING OF THE TERM “STABULARIUS” IN SOUTH AFRICAN LAW - Pieter Carnelley; Shannon Hoctor (Obiter, 2015)
What does “stabularius” mean? In Swart v Shaw t/a Shaw Racing Stables (1996 (1) SA 202 (C)), the court had to determine the meaning of the term “stabularius” and how this term, originally found in Roman law as set out in the Praetorian Edict (D 4 9 0), is to be applied in South African law. The Edict states that there is an undertaking by “sea-carrier, inn-keeper and a stable-keeper that their customers’ goods would be safe while on their ship or their premises”. The implementation of this principle was further elaborated upon in Roman-Dutch law, which increased the ambit of the defence against the Edict as compared to that which was applied previously. However, the Edict itself was still dogmatically applied. The court in Swart v Shaw challenged the prevailing interpretation of “stabularius” as “stable-keeper”, holding that it should not be interpreted as such but that it should rather mean an “ignoble inn-keeper”. Using Swart v Shaw as a basis for the discussion, this note will firstly assess whether this interpretation is correct and, secondly, it will determine what consequences will flow from such interpretation. The question is then posed whether it is fair to apply the Edict to certain situations but not to others. This ultimately determines whether, and to what extent, the Edict is still relevant in South Africa.